LARANGAN JABATAN RANGKAP KOMISARIS BUMN DITINJAU BERDASARKAN HUKUM PERSAINGAN USAHA DI INDONESIA - Darcyando Geodewa; Ditha Wiradiputra (Institut Pendidikan Tapanuli Selatan, 2023)
One of the assessments of the dominant position of a business actor can be conducted based on the affiliation relationship of the business actor with other business actors, where an affiliation regulated in Law of the Republic of Indonesia Number 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition is interlocking directorate and cross-share ownership. Interlocking directorate is not permitted when a person simultaneously holds a position as directors or commissioners in two (or more) companies at the same time, where the companies are in the same relevant market, have close relationship in the type and or field of business, or can jointly control the market share of certain services and or goods. The legal issue regarding interlocking directorate of SOE commissioners arose when the Regulation of Minister of SOE PER-10/MBU/10/2020 came into effect which allows members of the board of commissioners of SOEs to have interlocking directorate with certain conditions. This research is a normative legal research that examines the interlocking directorate prohibition of members of board of commissioners of SOEs based on business competition law in Indonesia.